Food Processing Technologies to Develop Functional Foods With Enriched Bioactive Phenolic Compounds in Cereals - Kasote, Deepak; Tiozon, Rhowell N.; Sartagoda, Kristel June D.; Itagi, Hameeda; Roy, Priyabrata; Kohli, Ajay; Regina, Ahmed; Sreenivasulu, Nese (Frontiers in Plant Science, 2021)
Cereal grains and products provide calories globally. The health benefits of cereals attributed to their diverse phenolic constituents have not been systematically explored. Post-harvest processing, such as drying, storing, and milling cereals, can alter the phenolic concentration and influence the antioxidant activity. Furthermore, cooking has been shown to degrade thermo-labile compounds. This review covers several methods for retaining and enhancing the phenolic content of cereals to develop functional foods. These include using bioprocesses such as germination, enzymatic, and fermentation treatments designed to enhance the phenolics in cereals. In addition, physical processes like extrusion, nixtamalization, and parboiling are discussed to improve the bioavailability of phenolics. Recent technologies utilizing ultrasound, micro- or nano-capsule polymers, and infrared utilizing processes are also evaluated for their effectiveness in improving the phenolics content and bio-accessibility. We also present contemporary products made from pigmented cereals that contain phenolics.